The Impact of ChatGPT on Academic Writing Skills and Knowledge: An Investigation of Its Use in Argumentative Essays - Khampusaen, Dararat (LEARN Journal: Language Education and Acquisition Research Network, 2025)
This study investigates the impact of ChatGPT on EFL students' argumentative writing development of 30 third-year English majors. The research examines writing quality improvements, student perceptions, and patterns of AI tool usage across a 16-week period. This study employed a mixed-methods design to investigate both students' writing development and their perceptions of AI integration. Writing development was assessed through comparative analysis of participants' first and fifth drafts as pre-test and post-test assessments, while perceptions data were collected through a validated 17-item questionnaire (Cronbach's α = 0.89) focusing on confidence and concerns in AI-assisted writing. Essays were evaluated using an adapted AIAS framework focusing on six dimensions: content, organization, language use, critical thinking, AI integration, and academic integrity. The quantitative analysis revealed significant enhancements in writing performance, with the most substantial improvements in academic integrity (+3.0 points. Furthermore, the thematic analysis of the draft comparisons demonstrated marked progression in argument construction, evidence integration, and academic voice. This research provides insights for developing pedagogical frameworks that optimize AI integration while fostering independent writing competencies.